Evidence of Sustainable Learning from the Mastery Rubric for Ethical Reasoning - Rochelle E. Tractenberg; Kevin T. FitzGerald; Jeff Collmann (MDPI AG, 2016)
Interest in sustainable learning has been growing over the past 20 years but it has never been determined whether students-whose learning we are trying to sustain-can perceive either the sustainability of their learning or any of the features of this construct. A four-item survey was developed based on a published definition of "sustainable learning", and was sent to the 12 graduate students who have completed a new seminar in ethical reasoning. A thematic analysis of the narrative responses was submitted to a degrees-of-freedom analysis to determine the level and type of evidence for student perception of sustainability. Respondents (n = 9) endorsed each of the four dimensions of sustainable learning-and each gave examples for each dimension outside of, and after the end of, the course. One respondent endorsed all dimensions of sustainable learning, but was uncertain whether the course itself led to one particular sustainability dimension. While these results must be considered preliminary because our sample is small and the survey is the first of its kind, they suggest that graduate students can and do perceive each of the four features of sustainability. The survey needs refinement for future/wider use; but this four-dimensional definition could be useful to develop and promote (and assess) sustainable learning in higher education.